Understanding the complex phage-host interactions in biofilm communities - Pires, Diana Priscila Penso (2021)
Bacteriophages and bacterial biofilms are widely present in natural environments, a fact that has accelerated the evolution of phages and their bacterial hosts in these particular niches. Phage-host interactions in biofilm communities are rather complex, where phages are not always merely predators but also can establish symbiotic relationships that induce and strengthen biofilms. In this review we provide an overview of the main features affecting phage-biofilm interactions as well as the currently available methods of studying these interactions. In addition, we address the applications of phages for biofilm control in different contexts.